2021
DOI: 10.1186/s13023-021-02061-3
|View full text |Cite
|
Sign up to set email alerts
|

The IDeaS initiative: pilot study to assess the impact of rare diseases on patients and healthcare systems

Abstract: Background Rare diseases (RD) are a diverse collection of more than 7–10,000 different disorders, most of which affect a small number of people per disease. Because of their rarity and fragmentation of patients across thousands of different disorders, the medical needs of RD patients are not well recognized or quantified in healthcare systems (HCS). Methodology We performed a pilot IDeaS study, where we attempted to quantify the number of RD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 37 publications
(27 reference statements)
0
41
0
Order By: Relevance
“…This can lead to increased healthcare expenditures impacting not only patients, but also HCS and providers, thus reducing the efficiency of care. In addition, the increased burden on health providers, long diagnostic odysseys, the need for specialized care, and the high price of approved treatments can result in disproportionately high health care costs [ 18 , 19 ]. These costs are often borne by the patient/families, health insurers or in countries where social medicine is provided, the government.…”
Section: Resultsmentioning
confidence: 99%
“…This can lead to increased healthcare expenditures impacting not only patients, but also HCS and providers, thus reducing the efficiency of care. In addition, the increased burden on health providers, long diagnostic odysseys, the need for specialized care, and the high price of approved treatments can result in disproportionately high health care costs [ 18 , 19 ]. These costs are often borne by the patient/families, health insurers or in countries where social medicine is provided, the government.…”
Section: Resultsmentioning
confidence: 99%
“…Splinter et al [ 25 ] compared the health care cost before and during the diagnosis evaluation period and found the latter to be only 6–7% of the total cost. Recently, Tisdale et al [ 307 ] performed a pilot study on 14 rare diseases within four different healthcare system databases to estimate direct medical costs. They found that per patient direct medical costs of rare diseases are about 3–5 times higher than age matched controls, highlighting the urgent need for early and accurate diagnosis for rare disease patients that may reduce the costs associated with misdiagnosis or missed opportunities for intervention at an appropriate time.…”
Section: Challengesmentioning
confidence: 99%
“…The future of EoE management will require personalized care which can be delivered by AI. Preventative measures are possible with an AI that flags patients at risk using data such as birth and family history, biomarker profiles, as well as genome and microbiome data, and such models have proven useful in application to other rare disorders [10,46]. Regression models have been used to predict features missing from shallow biopsies, and AI will likely decrease the percent of equivocal biopsies [47].…”
Section: Future Applicationmentioning
confidence: 99%